Reproductive patterns of Cynopterus brachyotis (dog-faced fruit bat) in Bintulu, Sarawak - Abdullah, Ibrahim; Musa, Norfahiah; Mohd Top, Marina; Zakaria, Mohamed (Universiti Putra Malaysia Press, 2013)
Reproductive period is a critical phase for most living organism. However, the influence of environmental condition on the reproductive pattern of Chiroptera in Malaysia is not well studied. A study on the reproductive patterns of dog-faced fruit bat, Cynopterus brachyotis, was conducted at Universiti Putra Malaysia, Bintulu Campus, Sarawak. Bats were captured in a planted forest and mixed dipterocarp forest using mist-nets for a period of 14 months from January 2009 to February 2010. The reproductive status was determined based on morphology of the bats. Five (I-Minor testes enlargement, no epididymal distention, II-Testes at or near maximal enlargement, no epididymal distention, III-Testes regressed, cauda epididymal distented, IV-Testes not regressed, cauda epididymal distented and V-No testiscular or epididymal enlargement) and four (I-Possibility pregnant, II-Lactating, III-Post-lactating and IV-Not reproductively active) categories of the reproductive status were categorized for the male and female C. brachyotis, respectively. Bats reproduce at all time of the year and the peak periods are associated with the rainy seasons. The first peak of reproduction (pregnancy and lactation) occurred in January to April 2009 and second peak in June to November 2009. The highest frequency of pregnancy and lactation female coincided with the fruit abundance. The results indicated that C. brachyotis performed a non-seasonal reproductive pattern. The findings are important in understanding the reproductive biology of bats and in protecting this ecologically important and diverse group of mammals.